Descripción del uso de diatomeas como correctores de suelos ácidos - Vera Acosta, José Andrés (2020)
The present work carried out represents a contribution to reveal relevant information from the research and work done on diatoms and their use as acid soil correctors. Climate and parent material are the main factors that have defined the great diversity of soils in Ecuador. In general, old soils (which do not develop on volcanic material) are acidic, of low fertility and high content of interchangeable aluminum. There is also an aggressive deterioration of soil resources in the country. Diatoms are single-celled microscopic organisms that belong to the Heterokontophyta division and the Bacillariophyceae class, they are microalgae. It is the most diverse group of algae and is found in both marine and continental environments. Diatomaceous earth is a material formed by fossilized algae typical of fresh and marine waters. As a pH regulator in acidic soils, as the ions increase, the content of aluminum and iron decreases, and in this way it acts as a regulator of the pH of the soil through an electrostatic mechanism that "blocks" Fe, Al and Mn, elements that cause acidity in soils. There are several types of diatoms. Aulacoseira granulata, rich in silicon (42%), belongs to freshwater diatoms. It is navicular (canoe-shaped) and includes individuals with round ends and lanceolate valves, fluted in the middle zone in the opposite direction to the poles. Soil microorganisms are the most important components of the soil. They constitute its living part and are responsible for the dynamics of transformation and development. The amount of application of diatoms to correct acidic soils will depend on the level of acid in the soil, according to several authors, which indicates that 5 kg of diatoms dissolved in 100 liters of water per hectare and in powder form should be applied. 8 kg per hectare.